An unusual case of haemoperitonium and bladder invasion due to placenta percreta in the third trimester mimicking threatened uterine rupture - Khan, Shama; Singh, Kavita N.; Ghanghoriya, Vineeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Placenta praevia percreta is a rare but potentially lethal complication of pregnancy. It has an increasing clinical significance due to its association with previous caesarian section and uterine curettage. Herein we report a patient with placenta percreta, presenting in the emergency as 33 weeks of gestation with acute pain in abdomen and haemorrhagic shock, mimicking silent spontaneous uterine rupture, managed by emergency caesarian section followed by cesarian hysterectomy and bladder repair.